An investigation of affect responses drawn from South African tertiary level visual communication students by means of illustrating the corporeal feminine through comic book art. - Hunter, Katherine (Stellenbosch : Stellenbosch University, 2019)
Thesis (MA)--Stellenbosch University, 2019.